Pengaruh Brand Community Terhadap Loyalitas Merek Juventus Football Club (Studi pada Juventus Club Indonesia Chapter Surabaya) - Aries Budi Prasetyo (Jurnal Ilmiah Mahasiswa FEB, 2014)
Football is a sport that is very much admired by the people of the world , especially in Indonesia . In Indonesia Football is a sport that involves almost the entire population in Indonesia , well who does not like football and are very fond of football , they will follow every single show held in Indonesia and International This study uses multiple regression analysis with SPSS version 18.1. This data collection The method uses a questionnaire to members of the community Juventus Club Indonesia Chapter Surabaya Questionnaire method is used to determine what factors are behind the more brand loyalty Juventus Football Club so members of the community decided to remain loyal to use trademark Juventus Football Club.Questionnaires were distributed to 80 questionnaire. The results showed six variables: the legitimacy of the brand community, opposition brand loyalty, celebrating the history of the brand, brand share, integrate and maintain members, and assist in the use of the brand, which is a significant brand loyalty opposition, share the brand story, integrate and retain members, and assist in the use of the brand. Keywords: brand loyalty, brand community